ELECTRONIC LEARNING TOOLS WITH GAMIFICATION ELEMENTS - Asaulenko, Е. В; Pak, Н. И. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The concept of «game mechanics» is analyzed. A conceptual model of an automated interactive software environment using gamification elements is presented. Destructive strategies generated by various game mechanics are considered. Some ways to deal with destructive strategies are listed. The article describes the experience of using gamification elements in the software environment for teaching students of secondary vocational education to solve physical problems. On the basis of experimental work, the effectiveness of using game mechanics to form a stable internal motivation of students to systematically solve problems is shown. This article may be useful for developers of electronic learning tools